2020
DOI: 10.1016/j.schres.2020.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, behavioural and neural validation of the PANSS amotivation factor

Abstract: Negative symptoms in schizophrenia have been suggested to map onto two distinct factors-amotivation and diminished expression. Only recently, two-factor solutions for measuring negative symptoms have been proposed for the Positive and Negative Symptom Scale (PANSS), the most commonly used scale to assess the psychopathology of patients with schizophrenia. We aimed to validate the PANSS two-factor structure on a clinical, behavioural and neural level. For this multi-level validation, we reanalysed several datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The reported two-factor structure comprise of: (1) an apathy domain, including emotional withdrawal, passive social withdrawal, and active social avoidance and (2) a diminished expression domain, including blunted affect, poor rapport, lack of spontaneity, and motor retardation (13,14). This structure has been supported by a confirmatory factor analysis in an adult schizophrenia sample (19), and validated against corresponding subdomains of the Brief Negative Symptom Assessment Scale (20). Investigations of the two negative symptom domains, separately, have reported differential associations with other clinical aspects of psychotic disorders and neurobiology, including functional outcome (21), cognitive impairments (22,23), neuronal task activation (24), and white matter connectivity (25).…”
Section: Introductionmentioning
confidence: 81%
“…The reported two-factor structure comprise of: (1) an apathy domain, including emotional withdrawal, passive social withdrawal, and active social avoidance and (2) a diminished expression domain, including blunted affect, poor rapport, lack of spontaneity, and motor retardation (13,14). This structure has been supported by a confirmatory factor analysis in an adult schizophrenia sample (19), and validated against corresponding subdomains of the Brief Negative Symptom Assessment Scale (20). Investigations of the two negative symptom domains, separately, have reported differential associations with other clinical aspects of psychotic disorders and neurobiology, including functional outcome (21), cognitive impairments (22,23), neuronal task activation (24), and white matter connectivity (25).…”
Section: Introductionmentioning
confidence: 81%
“…We calculated the subdimension of negative symptoms, according to the PANSS five-factor model 44 . In addition, we also used the PANSS Amotivation factor 45 , 46 , which highly correlated with Brief Negative Symptoms Scale (BNSS 47 ) and effort-based decision-making 48 . The following cognitive tests were administered to all participants: Letter Digit Sequencing span of WAIS-IV, revised shopping test 49 , and the fNART.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, concluding from available data (Shaffer et al, 2015;Abram et al, 2017;Walton et al, 2018;Li et al, 2018;Bègue et al, 2020;Brady et al, 2019, Guessoum et al, 2020, Kaliuzhna et al, 2020, we hypothesize, that the most robust association between avolition/anhedonia/asociality symptoms (and/or social amotivation factor) and abnormal WM changes will be manifested within the fronto-temporo-parietal regions, such as orbitofrontal cortex, cingulate gyrus, middle and superior temporal gyrus, and precuneus.…”
Section: Introductionmentioning
confidence: 96%
“…The concurrent validity of both BNSS and PANSS is high and a recent study (Kaliuzhna et al, 2020) revealed that both amotivation factors reach a relatively high negative association with diminished left ventral striatal activation. However, the effect sizes for BNSS were much higher and the authors emphasize that the use of specialized scales like BNSS is crucial in MRI studies directly addressing negative symptoms (Kaliuzhna et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation